Effects of a family-focused dyadic psychoeducational intervention for stroke survivors and their family caregivers: a pilot study - Huanyu Mou; Stanley Kam Ki Lam; Wai Tong Chien (BMC, 2022)
Abstract Background Stroke is one of the leading causes of disability in China and worldwide, affecting the health and well-being of both stroke survivors and their family caregivers (i.e. stroke dyads). Dyadic interventions targeting both as active participants can be beneficial for the dyads' health and well-being. Psychoeducation is a potentially acceptable approach to developing participants' knowledge about their disease management to promote their recovery. This study aims to explore the feasibility, acceptability, and preliminary effects of a family-focused dyadic psychoeducational intervention for stroke dyads. Methods This study was a single-blinded, parallel-group randomised controlled trial. Totally, a convenience sample of 40 stroke dyads was recruited. The intervention included three in-hospital face-to-face education sessions and four weekly post-discharge follow-up telephone counselling sessions. Feasibility was assessed by the rates of recruitment, attritions, and adherence to the intervention. Acceptability was evaluated via semi-structured qualitative interviews. Preliminary intervention effects were evaluated on primary (survivors' functioning and caregivers' burden) and secondary (caregivers' competence and dyads' coping, depressive and anxiety symptoms, family functioning, and dyadic relationship) outcomes. Results Intervention feasibility was established with satisfactory recruitment (76.9%), attrition (10%), and intervention completion (75%) rates. Qualitative interviews suggested that the intervention was acceptable and useful to stroke dyads. The intervention effects on survivors' functioning were significant in the memory and thinking (F = 8.39, p = 0.022, η = 0.18) and mobility (F = 5.37, p = 0.026, η = 0.12) domains, but not significant on their overall functioning (F = 2.39, p = 0.131). Caregiver burden in the intervention group was significantly greater reduced at post-test than the control group, with a large effect size (F = 7.55, p = 0.013, η = 0.28). For secondary outcomes, this intervention suggested a significant effect on caregivers' competence (F = 5.20, p = 0.034, η = 0.22), but non-significant effects on other outcomes. Conclusions The family-focused dyadic psychoeducation programme was feasible and acceptable for stroke dyads and showed preliminary effects for stroke dyads. These findings support a larger-scale controlled trial to further examine its intervention effects over a longer-term follow-up. Trial registration This study was retrospectively registered as a randomised controlled trial in the ISRCTN Registry. Registration Date: October 10, 2022. Registration Number: ISRCTN18158500.